The Impact Of Job Ambiguity And Work Stress As Intervening Variable On Turnover Intention Among Employees - Martini Martini (Universitas Muhammadiyah Semarang, 2024)
The purpose of this study is to investigate how employees' intentions to leave their jobs are affected by job uncertainty and work stress. The key problem addressed is how these variables influence an employee's decision to leave their job. Data was gathered using a quantitative research methodology and a structured questionnaire given to 200 employees in Jakarta from different industries. To guarantee sample variety, a random sampling technique was used. The results show that job ambiguity and work stress both significantly raise the intention to leave the company, suggesting that unclear job duties and high levels of stress might increase employee discontent. This study emphasizes how critical it is to address these elements in organizational settings in order to raise general workplace morale and staff retention. The knowledge gathered from this study can help managers and HR specialists create plans to reduce uncertainty and stress, creating a more encouraging work atmosphere that rewards commitment and loyalty from employees.